Reply to Comment by Borisenko et al. on article `A de Haas-van Alphen study of the Fermi surfaces of superconducting LiFeP and LiFeAs' - Putzke, C; Coldea, A; Guillamon, I; Vignolles, D; McCollam, A; LeBoeuf, D; Watson, MD; Mazin, I; Kasahara, S; Terashima, T; Shibauchi, T; Matsuda, Y; et al. (2011)
Recently, Borisenko et al have posted a Comment (arXiv:1108.1159) where they suggest an alternative interpretation of our de Haas-van Alphen (dHvA) measurements on the superconductor LiFeAs. In our original paper (arXiv:1107.4375) we concluded that our measurements of the bulk Fermi surface were not consistent with the surface bands observed thus far by ARPES. Borisenko et al dispute this and suggest the two measurements are consistent if some of the orbits we observe are due to magnetic breakdown. We argue here that this scenario is inconsistent with the experimental data and therefore that our original conclusion stands.